Komin słoneczny - studium przypadku = Solar chimney - a case study - Nakielska, Magdalena (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The policy of countries in the world, is reduce energy intensity and increasing the share of renewable energy sources in many industries. This also applies to the construction industry. Therefore looking for new materials and technology, heating, cooling and ventilation. The article presents the problem of ventilation systems that use solar chimney. The article presents the problem of ventilation systems, using solar chimney, shown in the example of the functioning of the natural ventilation of the solar chimney.
Keywords: wentylacja grawitacyjna; komin słoneczny; wspomagania wentylacji; natural ventilation; solar chimney; assisted natural ventilation